Run‐of‐river power plants in Alpine regions: Whither optimal capacity?. Issue 7 (26th July 2015) - Lazzaro, G.; Botter, G.
Abstract: Although run‐of‐river hydropower represents a key source of renewable energy, it cannot prevent stresses on river ecosystems and human well‐being. This is especially true in Alpine regions, where the outflow of a plant is placed several kilometers downstream of the intake, inducing the depletion of river reaches of considerable length. Here multiobjective optimization is used in the design of the capacity of run‐of‐river plants to identify optimal trade‐offs between two contrasting objectives: the maximization of the profitability and the minimization of the hydrologic disturbance between the intake and the outflow. The latter is evaluated considering different flow metrics: mean discharge, temporal autocorrelation, and streamflow variability. Efficient and Pareto‐optimal plant sizes are devised for two representative case studies belonging to the Piave river (Italy). Our results show that the optimal design capacity is strongly affected by the flow regime at the plant intake. In persistent regimes with a reduced flow variability, the optimal trade‐off between economic exploitation and hydrologic disturbance is obtained for a narrow range of capacities sensibly smaller than the economic optimum. In erratic regimes featured by an enhanced flow variability, instead, the Pareto front is discontinuous and multiple trade‐offs can be identified, which imply either smaller or larger plants compared to the economic optimum. In particular, large capacities reduce the impact of the plant on the streamflow variability at seasonal and interannual time scale. Multiobjective analysis could provide a clue for the development of policy actions based on the evaluation of the environmental footprint of run‐of‐river plants. Key Points: We set a method to trade between profitability and hydrologic impact of RoR plants Pareto‐optimal and efficient capacities are affected by the flow regime Streamflow variability is less impacted by large plants